Case report of a 3-year-old girl with pleuropulmonary blastoma and family history of a tumor predisposition syndrome with c. 2830 gene mutation in DICER1 - Y. Puckett; J. Howe; D. Vane; A. Agarwal; J.R. Batanian; J. Greenspon (Elsevier, 2015)
Pleuropulmonary blastoma (PPB) is a childhood mesenchymal pleural-based tumor that is associated with a germline mutation in DICER1 gene in familial PPB. It occurs most commonly in children between the ages of 2 and 5. Approximately 25% of patients have familial cancer syndrome which can include different combinations of PPB, lung cysts, thyroid tumors, cystic nephroma, Wilms tumor, embryonal rhabdomyosarcoma, ovarian Sertoli-Leydig cell tumors, juvenile granulosa cell tumor, gynandroblastoma, medulloblastoma, other childhood central nervous system tumors, nasal chondral mesenchymal hamartoma, and small bowel polyps. Our case report presents a child diagnosed with PPB with maternal history of bilateral ovarian Sertoli-Leydig cell tumors and papillary carcinoma of the thyroid. Molecular analysis performed on the patient and mother showed a specific gene change (c. 2830) in the DICER1 gene. The patient underwent surgical resection of the tumor and five cycles of chemotherapy. Despite this aggressive treatment, she eventually succumbed to brain metastases and was made comfort care after suffering a massive brain hemorrhage several months after the initial diagnosis of her disease.